INTERNATIONAL SCALE INTEGRATED THEMATIC TOURISM DESTINATION DESIGN, KOKAS DISTRICT AND ARGUNI DISTRICT IN FAKFAK DISTRICT - Jhon Iha; Titis Istiqomah; Choirul Anam; Christina Wulansari (Jurnal Scientia, 2023)
Arguni District and Kokas District have very exotic marine natural potential, rich history of civilization, and very abundant fishing resources. Almost all villages in this district can only be reached by boat transportation across the sea with very beautiful natural views. The research aims to find a form of implementation of accelerated development of integrated ecotourism and creative economy based on analysis of innovation, motivation and competence of local youth drivers. The research was carried out from May – October 2023. The research method was descriptive with a combination approach of quantitative and qualitative analysis. Data was obtained through a direct survey of respondents who had been determined deliberately. The data obtained is given a weight value based on assessment indicators obtained from the results of preliminary research. Test the validity and reliability of the data in a gradual and structured manner using a triangulation and role sharing approach . The research results are presented in the form of a spider web diagram equipped with illustrations of shift share gap values, Ishikawa diagrams with weighting, Pearson correlation analysis , and regression equation models obtained from the SPSS version 2.3 statistical tool.